Assessment of biodiesel as an alternative fuel for shipping industry - Lim, Wei Juan (2019)
In recent years, the world has geared towards a reduction in carbon emissions in view of rising temperatures, including the maritime industry. Therefore, the maritime industry has worked towards cutting shipping’s emission to air and reduce its carbon footprint. Decarbonization will be one of the megatrends towards shaping the industry in light of IMO greenhouse gas (GHG) strategy. In responding towards decarbonization, this report will offer some insights into the potential of biodiesel as a solution towards decarbonizing, and how they might develop the shipping industry towards 2030. Many studies have investigated biofuel technologies and their environmental impacts. However, minimal attention was given to the assessment of biofuels’ potential and sustainability in the maritime industry or relate to fuel expectations of the stakeholders from the maritime industry. Therefore, this report aims to conduct a holistic study on biodiesel’s potential in the maritime industry through economic, technical, social and environmental considerations 2030. During the project, a literature review is being conducted on 2 ends. Firstly, the literature review would cover engines, conventional marine fuel, and regulations adopted by the International Maritime Organization (IMO). Secondly, the literature review will cover the overview of biofuels and provide a more in-depth study on biodiesel and its marine application. A questionnaire is being conducted to select the appropriate criteria to assess biodiesel’s potential. This is followed by a discussion on the following criteria and the research implications. Finally, the conclusion would cover the overview of this study on biodiesel’s potential as an alternative marine fuel as well as provide recommendations for future works.